PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP MINAT BELI ULANG PRODUK SYAHI HALEEB - Fahmi Firdausi; Agustiono Agustiono (Universitas Ciputra Surabaya, 2021)
The food and beverage business in Indonesia is positive because it is able to contribute the highest Gross Domestic Product (GDP) among the sub-sectors under other creative economy categories. This phenomenon is certainly a good opportunity for food and beverage business actors such as Syahi Haleeb. Syahi Haleeb sells spiced milk tea beverage products located in Surabaya. This study aims to determine the effect of product quality and price on the intention to repurchase Syahi Haleeb's products. This study uses a quantitative approach using purposive sampling technique. The population in this study are consumers of Syahi Haleeb's products. The sample used in this study were 97 respondents. Data collection method using a questionnaire with a Likert scale and data analysis using linear regression analysis. The results in this study show that product quality has a positive and significant effect on repurchase interest, price has a significant effect on repurchase interest.